Institutional ownership, volatility and dividends - Rubin, Amir; Smith, Daniel R. (Journal of Banking & Finance, 2009)
We find that the sign of the correlation between institutional ownership and volatility depends on the firm’s dividend policy: institutional ownership is negatively (positively) related to volatility among non-dividend (dividend) paying stocks. The empirical results are consistent with an interaction between institutional preference for low volatility and the tendency of higher levels of institutional ownership to increase volatility through their trading behavior. This result is robust to many control variables and possible endogeneity concerns. Supporting our conjecture that institutions herd on dividend signals we find that the correlation between turnover and institutional ownership is higher for dividend paying stocks, and that the positive correlation between turnover and institutional ownership is higher on dividend declaration days. Finally, we also find that the level of institutional ownership drops following an increase in volatility for both dividend payers and non-payers, and that volatility rises following increased institutional ownership for dividend paying stocks.